Biological sex as a variable in immunity does not affect parabolic flight-induced alterations in immune responses - Moser, Dominique; Buchheim, Judith-Irina; Biere, Katharina; Matzel, Sandra; D´Amico, Federico; Choukér, Alexander; Woehrle, Tobias; Feuerecker, Matthias (Frontiers in Immunology, 2025)
The present era of spaceflight is accompanied by two meaningful breakthroughs. The access to in-orbit missions for civilians and the increasing enrolment of female astronauts require detailed investigations on the impact of gravitational stress on human physiology with focus on sex-specific differences. To assess the responsive capacities of innate and adaptive immunity in this context, functional characterizations were performed in women and men in a parabolic flight study. Blood and saliva were collected 1 month prior and on the day before the flight, as well as directly after flight and on the following day. Leukocyte proportions were quantified, and NETosis as well as phagocytic activity was tested. The impact of gravitational stress on the ability to mount a functional immune response was examined by a 6-h whole-blood incubation assay with subsequent analysis of leukocyte surface activation marker expression and cytokine secretion. Parabolic flight induced a temporary increase in granulocyte proportions, which however did not influence NETosis and phagocytosis. Throughout the flight week, leukocyte activation and cytokine secretion patterns remained unaltered in response to antigen stimulation. No differences were found regarding the direction or intensity of immune response either in women or in men. However, when comparing effects 1 month before flight and the flight week, immune responses were still present but remarkably weaker during flight week, which was independent of cortisol levels. Altogether, this study elicited two important findings. Firstly, no sex-specific increased risk exists for immune dysregulation by acute gravitational stress. Secondly, merely changing the day to day surrounding dampens crucial immune responses, which requires further investigations.